(untitled) (European Journal of Pure and Applied Mathematics, 2023)
The purpose of the present article is to introduce the notion of (Λ, s)-closed sets. Especially, some properties of generalized (Λ, s)-closed sets are obtained. Several characterizations of some low separation axioms are given. Characterizations of (Λ, s)-extremally disconnected spaces are investigated. Furthermore, some characterizations of almost (Λ, s)-continuous functions are discussed.